ÇOK KATLI BETONARME YAPILARIN DEPREM DAVRANIŞINDA DOLGU DUVAR ETKİSİNİN İNCELENMESİ - DEMİR, TUBA (Fırat Üniveristesi, 2016)
Bu çalışmada, dolgu duvarların betonarme yapı sistemine olan katkısını belirlemek amaçlanmıştır. Bunun için 3 katlı, 5 katlı ve 7 katlı betonarme yapılar modellenmiştir. Bu modeller kendi içinde üç farklı şekilde yeniden tasarlanmıştır. Birinci model tüm katlarının, tamamen dolgu duvarsız olduğu çerçeve modelidir. İkinci model ilk katında dolgu duvarların olmadığı, diğer katlarında ise dolgu duvarların olduğu çerçeve modelidir. Üçüncü model ise tüm katlarında dolgu duvarların olduğu modeldir. Bu şekilde dokuz farklı yapı modellenmiştir. Bu modellerin tümü, her iki yönde iki açıklığa sahip olup, TS500 ve Türk Deprem Yönetmeliği 2007'de esas alınarak tasarlanmış ve SAP2000 programı kullanılarak üç boyutlu şekilde modellemesi yapılmıştır. Dolgu duvarlı olarak tasarlanan modellerde, dolgu duvarlar eşdeğer basınç çubuğu şeklinde tanımlanmıştır. Tüm modeller için doğrusal elastik hesap yöntemi kullanılarak analizler yapılmıştır. Analiz sonucunda yapıların göreli kat ötelemeleri, yer değiştirme değerleri belirlenmiş ve tüm modeller için ayrı ayrı kıyaslama yapılarak grafikler çizilmiştir. Elde edilen sonuçlara göre de dolgu duvarların sistemin rijitliğini ve dayanımını değiştirdiği görülmüştür. Bu doğrultuda, yapının performansının belirlenmesinde dolgu duvarların dikkate alınması gerektiği belirlenmiştir.

In this study, we aimed to determine the contribution to the reinforced concrete structure of the infill walls. For numerical application, three-storeys five-storeys and seven-story concrete structures were modeled in order to determine the contribution to the building system of infill walls. These models has been redesigned in three different type in itself. The first model is the frame model without completely infill walls of all story. The second model is the frame model which is absence of infill walls on the first floor and have infill walls on other floors. The third model is the frame model having infill walls on all floors. Nine different structures have modeled in this study. The scope of this study, the building models which has two apertures in both directions was modeled as three dimensions by using a computer program called SAP2000 on the basis of TS500 and Turkish Seismic Code, 2007. The infill walls were defined as the equivalent compression strut in the model which is designed as bare frame and infill walls. Linear analysis method was used for analyses of the models. For this purpose, the structure of interstory drifts, displacement values were determined and made separate comparisons were drawn graphics for all models. According to these results, infill walls have changed the rigidity and strength of the system. In this regard, it was determined that the infill walls must be considered in the determining of performance of structure.
Investigation of effect of infill walls in earthquake behavior of multi-storey concrete structures
Keywords: İnşaat Mühendisliği